Activated carbon doped with biogenic manganese oxides for the removal of indigo carmine. (15th January 2016) - Hu, Yichen; Chen, Xiao; Liu, Zhiqiang; Wang, Gejiao; Liao, Shuijiao
Abstract: Indigo carmine (IC) is one of the oldest, most important, and highly toxic dyes which is released from the effluents of many industries and results in serious pollution in water. In this study, the biogenic Mn oxides were activated by NaOH and then heated for 3 h at 350 °C to produce activated carbon doped with Mn oxide (Bio-MnOx -C), which were produced by culturing Mn (II)-oxidizing bacterial strain MnI7-9 in liquid A medium at 28 °C with 10 mmol/L MnCl2 . Bio-MnOx -C was characterized by SEM, TEM, IR, XPS, XRD, etc . It contained C, O, and Mn which comprised Mn (IV) and Mn (III) valence states at a ratio of 3.81:1. It had poorly crystalline ε-MnO2 with a specific surface area of 130.94 m 2 /g. A total of 0.1 g Bio-MnOx -C could remove 45.95 g IC from 500 mg/L IC solution after 0.5 h contact time. IC removal by Bio-MnOx -C included a rapid oxidation reaction and the removal reaction followed second-order kinetic equation. These results confirmed that Bio-MnOx -C could be a potential material for wastewater remediation. Highlights: A new eco-material (Bio-MnOx-C) was produced by carbonizing biogenic Mn oxides. Bio-MnOx-C contained C, O and Mn composed of Mn (IV) and Mn (III). IC removal by Bio-MnOx-C included a rapid oxidation reaction and slow adsorption. IC removal by Bio-MnOx-C followed second-order kinetic equation. Bio-MnOx-C can efficiently remove indigo carmine from waste water.